22. Iannis Xenakis/Le Corbusier: A Confrontation en sol dur - Guy Pimienta (Meta-Xenakis: New Perspectives on Iannis Xenakis’s Life, Work, and Legacies, 2024)
Le Corbusier was always able to surround himself with extremely competent people, which was one of his trademarks. As such, Pierre Jeanneret, Charlotte Perriand, Pierre Faucheux, and Iannis Xenakis were exemplary spearheads. Iannis Xenakis introduced himself to Le Corbusier in 1947 to work as an engineer in his Atelier, and the latter immediately integrated him into his AtBat, the agency he had created for the construction of the Housing Unit in Marseille. When Le Corbusier accepted the commission for La Tourette in 1953, he was deeply engaged in his Chandigarh project, so he entrusted the convent project to Xenakis, to whom he said: ‘I have a project which absolutely suits you, a very geometric project’. Xenakis simultaneously worked on the design of the convent and the composition of his first major musical work: Metastasis, contemporary with that of the undulating glass panes of La Tourette. In 1956, Le Corbusier asked Xenakis to design a Pavilion for the Brussels International Exhibition of 1958, a true contemporary form of synthesis of the arts, mathematics, and techniques which, with the passage of time, would appear as a manifesto of experimental architecture. When Xenakis claimed that his name be associated with that of Le Corbusier for the Philips Pavilion, their relationship deteriorated. The master found it fit to specify: ‘it is a common experience that the horse is convinced that it is driving the cart’. Iannis Xenakis demonstrates with this project that he is much more than a junior draftsman-engineer for a demanding architect. Notes in Le Corbusier's sketchbooks prove the importance he attached to the musician-architect. By firing him, Le Corbusier allowed the musical destiny of Iannis Xenakis to fully unfold.